Pre-vaccination seroprevalence of SARS-CoV-2 antibodies in the Volta Region, Ghana - Aninagyei, E.; Ayivor-Djanie, R.; Ampofo, W. K.; et al (IJID Regions, 2024)
Objectives: Before administration of the first dose of the AstraZeneca 2019 SARS-CoV-2 vaccine to selected pri oritized groups in the Volta regional capital of Ghana, we determined the pre-vaccination status of prospective recipients and established the baseline exposure status 1 year after the first case was reported. Methods: After informed consent, blood samples were collected for the detection of SARS-CoV-2 immunoglobulin (Ig) M/IgG antibodies using rapid diagnostic test kits. A total of 409 individuals (mean age 27 years) consented and participated in the study, comprising 70% students and others were health staff and educators who presented themselves for vaccination. Results: The overall exposure rate of SARS-CoV-2 was 12.7% (95% confidence interval [CI] 9.6-16.3). The preva lence of SARS-CoV-2 IgM and IgG were 4.2% (95% CI 2.4-6.6) and 5.6% (95% CI 3.6-8.3), respectively. IgM and IgG were detected in 2.9% (95% CI 1.5-5.1) of the respondents. The exposure rates were higher in participants over 40 years old (15.5%). Participants without a history of COVID–19–like symptoms had an exposure rate of 13.0% and those without any chronic diseases were 13.2%. Conclusion: Pre-vaccination exposure was relatively low and underscored the need for vaccination i to increase protection in communities and disease outcomes.
Research Article
Keywords: SARS-CoV-2; COVID-19; Vaccination; Exposure